How Flexible Is that Functional Form? Quantifying the Restrictiveness of Theories - Fudenberg, Drew; Gao, Wayne; Liang, Annie (The Review of Economics and Statistics, 2026)
Abstract We propose a restrictiveness measure for economic models based on how well they fit predefined synthetic data. This measure, together with a measure for how well the model fits real data, outlines a Pareto frontier, where models that rule out more regularities, yet capture the regularities that are present in real data, are preferred. To illustrate our approach, we evaluate the restrictiveness of models in two laboratory settings—certainty equivalents and initial play—and one field setting—takeup of microfinance in Indian villages. The restrictiveness measure reveals insights about each, including that some economic models with only a few parameters are very flexible.